UMP launches 8 Campus Sustainability Initiative Campaigns - Nor Salwana, Mohammad Idris (UMPSA, 2023)
PEKAN, 23 February 2023 - Universiti Malaysia Pahang (UMP) launched eight Sustainability Initiative Campaigns to raise awareness of campus residents to protect the environment in line with the realisation of the university’s aspiration towards a Sustainable Campus.